Gamma Oryzanol Alleviates High-Fat Diet-Induced Anxiety-Like Behaviors Through Downregulation of Dopamine and Inflammation in the Amygdala of Mice - Akter, Salina; Uddin, Kazi Rasel; Sasaki, Hiroyuki; Shibata, Shigenobu (Frontiers in Pharmacology, 2020)
Background: A high-fat diet (HFD) is often used to induce obesity and metabolic disorders which is closely associated with cognitive impairments and progression of several psychiatric disorders like anxiety. We have previously demonstrated the anxiolytic effect of γ-oryzanol (GORZ) in chronically restraint stressed mice. Objective: We studied the neurochemical and molecular mechanism that underlie the preventive effect of GORZ in HFD induced anxiety-like behaviors, monoaminergic dysfunction, and inflammation. Methods: 8 week old ICR male mice weighing 33-34 g were divided into following groups and free-fed for 8 weeks: Control (14% casein, AIN 93M); HFD and HFD + GORZ (0.5% GORZ). Body weight gain and feed consumption were checked weekly. The anxiolytic effects of GORZ were examined through open field test (OFT) and elevated plus maze (EPM) test. Central monoamines (5-hydroxy tryptamine (5-HT), dopamine (DA) and norepinephrine (NE)) with their metabolites (5-hydroxyindole acetic acid (5-HIAA), homovanillic acid (HVA), and 3-methoxy-4-hydroxyphenylglycol (MHPG), pro-inflammatory cytokines like Tumor necrosis factor- (Tnf-), and Interleukin 1-β (Il-1β) in the cerebral cortex and amygdala were examined using high-performance liquid chromatography-electrochemical detection (HPLC-ECD) and real-time reverse transcription-polymerase chain reaction (RT-PCR), respectively. Results: Mice feed with HFD for 8 weeks showed anxiety-like behaviors in association with HFD induced body weight gain. GORZ could potentially block HFD induced anxiety-like behaviors by significant improvement of the main behavioral parameters in behavioral tests with a slight reduction of the HFD induced body weight gain. Furthermore, GORZ treatment significantly downregulated the HFD induced upregulation of the dopamine levels in the amygdala of brain. Significant reduction of the relative mRNA expression of Tnf- and Il-1β were also observed in the amygdala of HFD + GORZ mice than in the HFD mice. Conclusions: Our findings strongly suggest that, 0.5% GORZ exerts anxiolytic effects possibly through downregulation of dopamine and pro-inflammatory cytokines Tnf- and Il-1β expression in chronic HFD exposure.